DynaBot: Dynamic Dota 2 Bot - Wanaldi Wanaldi; Yustinus Eko Sulistio; Johan Setiawan (Universitas Multimedia Nusantara, 2020)
This research was conducted to find out whether the Dynamic Scripting method that has been used before only on zeus characters can be generalized to be used on other characters on the Dota 2 game. Dynamic scripting works by using the rulebase where the rulebase contains actions that determine the actions performed by Artificial Intelligence (AI). In addition, some adjustments have been made to existing methods. To find out whether the performance of a generalized and adjusted model is better than the previous model, a test has been conducted where AI is made with dynamic scripting against AI provided by the valve in the Dota 2 game. In addition, AI has also been tested against humans. Then the performance of AI will be analyzed by comparing the winning ratio and several other supporting variables. The results of this study are that AI got a low winning percentage against standard AI and cannot win at all and give poor performance against humans. It can be concluded that the Dynamic Scripting method cannot be generalized to other characters in the Dota 2 game.